The Concept of God in Christianity as Seen Through Plato's Political Philosophy - LI, Gexin (Journal of Research for Christianity in China (JRCC), 2025)
What is God and His revelation? This is the fundamental question of all religious theology. Different religious theologies define their understanding of God and His revelation in distinct ways. These differing definitions directly influence the very nature of religious theology and religious faith. Therefore, exploring the concept of God is of paramount importance. This holds significant meaning for our understanding of Christianity, modernity, and classical philosophy.